Implementation of a Web-Based New Student Admissions Application (PPDB) at the Al-Kautsar Mauk Islamic Boarding School - Sugiyono, Sugiyono; Kristiyanto, Yogi; Radhiah, Ainatul; Simanjuntak, Dita Madonna (International Journal of Informatics, Economics, Management and Science; Vol 4 No 2 (2025): IJIEMS (August 2025), 2025)
The manual new student admissions (PPDB) process in Islamic boarding schools creates various obstacles such as time inefficiency, data input errors, and the risk of archive loss. This study aims to design and implement a web-based digital new student registration system at the Al-Kautsar Mauk Tahfidzul Qur'an Islamic Boarding School. The method used is software engineering with a Waterfall model approach, starting from needs analysis, design, development, and evaluation. The results show that the system can speed up the form filling process from 10–15 minutes to 2–3 minutes per participant, as well as improve the accuracy and security of data storage through the integration of Google Apps Script and Google Spreadsheets. The system allows admins to access and filter data in real-time without manual re-input. Trials were conducted through simulations with 10 participants and training was provided to admins to ensure smooth implementation. In conclusion, this web-based student admissions (PPDB) system has a positive impact on the efficiency, transparency, and readiness of Islamic boarding schools in facing the digitalization of educational administration.